Rapid Assessment of Seed Removal and Frugivore Activity as a Tool for Monitoring the Health Status of Tropical Forests - Boissier, Olivier; Bouiges, Axelle; Mendoza, Irene [UNESP]; Feer, Francois; Forget, Pierre-Michel (Wiley-Blackwell, 2014)
Ecological processes in tropical forests are being affected at unprecedented rates by human activities. Yet, the continuity of ecological functions like seed dispersal is crucial for forest regeneration. It thus becomes increasingly urgent to be able to rapidly assess the health status of these processes in order to take appropriate management measures. We tested a method to rapidly evaluate seed removal rates on two animal-dispersed tree species, Virola kwatae and V.michelii (Myristicaceae), at three sites in French Guiana with increasing levels of anthropogenic disturbance. We counted fallen fruits, fruit valves, and seeds of each focal fruiting tree in a single 1m2 quadrat, and calculated two indices: the proportion of seeds removed and the proportion of fruits opened by mammals. They both provide an indirect and rapid assessment of frugivore activity. Our results showed a significant decrease in the proportion of removed seeds (16%) and fruits opened (19%) at the most impacted site in comparison with the other two sites (79% for seeds, 60% and 35% for fruits). This testifies to an increased impoverishment of the primate and toucan communities at the disturbed sites. This standardized protocol provides fast information about the health status of the community of seed dispersers and predators and of their seed removal services. It is time- and cost-effective and is not species-specific, allowing comparisons among sites or over time. We suggest using it with the pantropical Myristicaceae and any other capsule-producing family to rapidly assess the health status of seed removal processes across the tropics.
Keywords: anthropogenic disturbance; French Guiana; frugivory; Myristicaceae; seed dispersal; tropical forests; Virola